2021
DOI: 10.1039/d1nj03217h
|View full text |Cite
|
Sign up to set email alerts
|

Field supported slow magnetic relaxation in a quasi-one-dimensional copper(ii) complex with a pentaheterocyclic triphenodioxazine

Abstract: A new copper(ii) complex (I) was obtained by the reaction of a sterically crowded 2,4-di-(tert-butyl)-9-chloro-benzo[5,6][1,4]oxazine[2,3-b]phenoxazine bridging ligand with Cu(ii) hexafluoroacetylacetonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 59 publications
4
19
0
Order By: Relevance
“…Cui et al 61 showed that five-coordinate [Cu(12-TMC)Cl][B(C 6 H 5 ) 4 ] (12-TMC = 1,4,7,10-tetramethyl-1,4,7,10-tetraaza cyclododecane) exhibits only one relaxation process in a distorted square pyramidal geometry of copper( ii ) ion. Korchagin et al 62 demonstrated that the quasi-one-dimensional Cu( ii ) complex [Cu(hfac) 2 (ClTDPO)] n (where hfac – hexafluoroacetylacetonate, ClTDPO – 2,4-di-( tert -butyl)-9-chloro-benzo[5,6][1,4]oxazine[2,3- b ]phenoxazine) relaxes through the combination of two-phonon Raman and one-phonon direct processes. Since these examples represent mutually unrelated compounds, more studies of structurally similar monometallic Cu( ii ) systems are needed to better understand the observed phenomena.…”
Section: Magneto-structural Correlations and Outcomementioning
confidence: 99%
See 2 more Smart Citations
“…Cui et al 61 showed that five-coordinate [Cu(12-TMC)Cl][B(C 6 H 5 ) 4 ] (12-TMC = 1,4,7,10-tetramethyl-1,4,7,10-tetraaza cyclododecane) exhibits only one relaxation process in a distorted square pyramidal geometry of copper( ii ) ion. Korchagin et al 62 demonstrated that the quasi-one-dimensional Cu( ii ) complex [Cu(hfac) 2 (ClTDPO)] n (where hfac – hexafluoroacetylacetonate, ClTDPO – 2,4-di-( tert -butyl)-9-chloro-benzo[5,6][1,4]oxazine[2,3- b ]phenoxazine) relaxes through the combination of two-phonon Raman and one-phonon direct processes. Since these examples represent mutually unrelated compounds, more studies of structurally similar monometallic Cu( ii ) systems are needed to better understand the observed phenomena.…”
Section: Magneto-structural Correlations and Outcomementioning
confidence: 99%
“…[56][57][58] Recent record value of 1.4 ms coherence time was demonstrated by Dai et al 56 for a (PPh 4 ) 2 [Cu(mnt) 2 ] (where mnt 2− is maleonitriledithiolate), after dilution in isostructural diamagnetic Ni(II) matrix and utilization of dynamic decoupling technique. As for the SIM behavior, the examples of compounds with experimentally determined field-induced slow magnetic relaxation with single d 9 Cu(II) ion are rather scarce, [59][60][61][62][63][64] whereas its origin is only partially understood. 48,49 To achieve the desired molecular magnetic behavior in S = 1 2 coordination systems, the following molecular design were proposed: (i) square planar coordination geometry; (ii) coordinating atoms devoid of nuclear spin; (iii) rigidification of the molecular architecture; (iv) minimization of the protons influence above a certain radius from the metal (the concept of spin diffusion barrier).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the superiority of these substances is also represented by the fact that Cu­(II) ions are already present in the human body, limiting the possibility of excessive immunological system response . Additionally, the introduction of a transition metal with unpaired electrons can also endow the obtained complexes with additional magnetic functionality such as SIM, SMM, or superparamagnetic behavior, which show slow relaxation of magnetization. …”
Section: Introductionmentioning
confidence: 99%
“…The precise and accurate measurement of temperature is of vital importance in both science and industry since temperature is a fundamental physical parameter. 1–8 More specifically, the methods of temperature measurement are divided into two different types: contact and noncontact depending on the measurement distance. 1,2,9,10 The conventional thermometers such as liquid-filled glass thermometers, bimetallic thermometers, thermocouples, and thermistors have been developed based on various kinds of temperature-dependent properties including volume, electric potential, electric conductance, and so on.…”
Section: Introductionmentioning
confidence: 99%